Quantification of intermuscular adipose tissue in the erector spinae muscle by MRI: agreement with histological evaluation of lipid - Rossi, Andrea (Obesity (Silver Spring), 2010)
Deposition of fat between skeletal muscle bundles and beneath the muscle fascia, recently called intermuscular adipose tissue (IMAT), is gaining attention as potential contributor to insulin resistance, metabolic syndrome, muscle function impairment and disability. The aim of this study was to compare IMAT as measured at the erector spinae level by MRI, a well-recognized gold standard method to evaluate fat content inside muscles, and histology estimates. In 18 healthy elderly men and women with a wide range of BMI (25.05–35.58 Kg/m(2)), undergoing elective vertebral surgery, IMAT within the erector spinae muscle was evaluated by MRI, by body composition using dual energy x-ray absorptiometry and histological evaluation of intraoperative biopsy sample. The concordance between IMAT/TA ratio evaluated by MRI and histological examination was analyzed employing Lin’s concordance correlation coefficient and the procedure proposed by Bland and Altman. Two threshold to distinguish between muscle and IMAT calculated respectively by 20% and 10% reduction of the gray level intensity evaluated by MRI from surrounding subcutaneous adipose tissue were used. With a 20% reduction, calculated IMAT/TA as evaluated by MRI on average exceeds histological evaluation by 21.79%, whereas by reducing the threshold by 10% agreement between MRI and histology improved with a 12.42% difference. Our data shows a good degree of concordance between IMAT assessment by magnetic resonance and histology and seems to show that agreement between the two methods could be improved by using a more restrictive threshold between muscle and fat.